1999
DOI: 10.1128/jvi.73.4.2994-3003.1999
|View full text |Cite
|
Sign up to set email alerts
|

HMG Protein Family Members Stimulate Human Immunodeficiency Virus Type 1 and Avian Sarcoma Virus Concerted DNA Integration In Vitro

Abstract: We have reconstituted concerted human immunodeficiency virus type 1 (HIV-1) integration in vitro with specially designed mini-donor HIV-1 DNA, a supercoiled plasmid acceptor, purified bacterium-derived HIV-1 integrase (IN), and host HMG protein family members. This system is comparable to one previously described for avian sarcoma virus (ASV) (A. Aiyar et al., J. Virol. 70:3571–3580, 1996) that was stimulated by the presence of HMG-1. Sequence analyses of individual HIV-1 integrants showed loss of 2 bp from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(47 citation statements)
references
References 30 publications
4
43
0
Order By: Relevance
“…In a few cases proteins have been identified that are candidates for affecting the integration step. Loss-of-function screens have been carried out using siRNA knockdowns, in which siRNAs targeting most human genes are assayed individually for their ability to either reduce or increase HIV infection (14) (53,54). Gain of function studies have been carried out by overexpressing cDNAs and assessing whether they increased or decreased HIV infection (163).…”
Section: Genome-wide Studies To Identify Candidate Host Factorsmentioning
confidence: 99%
“…In a few cases proteins have been identified that are candidates for affecting the integration step. Loss-of-function screens have been carried out using siRNA knockdowns, in which siRNAs targeting most human genes are assayed individually for their ability to either reduce or increase HIV infection (14) (53,54). Gain of function studies have been carried out by overexpressing cDNAs and assessing whether they increased or decreased HIV infection (163).…”
Section: Genome-wide Studies To Identify Candidate Host Factorsmentioning
confidence: 99%
“…The in vitro retroviral concerted DNA integration system (Fig. 1B,C) has previously been described by others [9,12,13]. It is composed of a linear donor DNA, a plasmid acceptor DNA and recombinant IN.…”
Section: Reconstitution Of the Concerted Dna Integration Assay In Vitromentioning
confidence: 99%
“…It is composed of a linear donor DNA, a plasmid acceptor DNA and recombinant IN. HMGI protein is added to the reaction because it has been found to enhance the concerted DNA integration reaction [12]. HMGI is a component of the HMGI(Y) protein (now referred as HMGa1).…”
Section: Reconstitution Of the Concerted Dna Integration Assay In Vitromentioning
confidence: 99%
See 2 more Smart Citations